Characterisation of the novel leucine rich repeat containing protein KIAA0644 - Carpenter, Susan (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2008)
This thesis reports the existence o f a novel leucine rich repeat containing protein annotated as KIAA0644 in the Kazusa DNA Research Institute database (www.Kazusa.or.jp). which was discovered in a study for proteins induced by Lipopolysaccaharide (LPS). This protein is expressed and highly conserved across species. It contains thirteen leucine rich repeats, a signal sequence, a fibronectin domain and a single spanning transmembrane region. It shows sequence similarity to Toll-like receptor, Nogo receptor and the Fibronectin leucine-rich transmembrane families. KIAA0644 is highly expressed in the brain, lung and ovary. RT-PCR results demonstrate that at the mRNA level KIAA0644 is induced by Lipopolysaccaharide (LPS). An antibody to the C terminus of the protein was raised and expression of KIAA0644 in the brain of human tissue samples was confirmed at the protein level. The protein was induced by LPS in the brain derived cell lines U373 and 1321-N1. KIAA0644 was also shown to be induced by LPS in the monocytic cell line THP1, in primary human peripheral blood mononuclear cells (PBMC), primary murine bone marrow derived macrophages (BMDM) and also in primary murine mixed glial cells.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin